Emissão de gases de efeito estufa e estoque de carbono no sistema solo-planta em função do sistema de produção e da aplicação superficial de corretivo da acidez - Alves, Michely da Silva [UNESP] (2016)
Crop rotation in no tillage can increase the stock of C in the soil and reduce emissions of greenhouse gases, though the use of soil amendments can undermine these benefits. Within this approach the work aimed to evaluate the annual emission of greenhouse gases and carbon storage in the soil-plant system due to the use of different corrective of soil acidity and crop rotations in long-tillage system duration. The survey was conducted in the Experimental Farm Lageado, belonging to the Faculty of Agricultural Sciences - UNESP, located in Botucatu (SP), and was conducted in the agricultural year 2014/2015. The plots consisted of four production systems (I. System "Safra intercropped with forage"; II System "Safra - offseason."; III System "Safra - Green manure / cover plant."; IV System "Safra Fallow." ) and the subplots by two sources of acidity corrective applied in October 2012 and a control (I - Correction with dolomitic lime II - Correction with calcium and magnesium silicate III - No correction). The gas samples for the determination of CO2 flows, N2O and CH4 from soil were performed after summer season 2014/2015 and further in the winter in 2015. The quantities of straw produced in each culture medium and supply of C and N added to the soil in winter and summer crops were analyzed. They also evaluated the stocks of C and N soil at 0-10, 10-20, 20-40 cm, and C and N microbial biomass at a depth of 0-10 cm. The results were submitted to analysis of variance (p <0.05) and the means were compared using the t test (p <0.05). Crop rotations System direct sowing and the use of lime did not increase the total organic carbon stocks and total N in the soil, as little of Microbial Biomass. Although not contributed to the stocks in the soil, crop rotation with systems involving forage and green manure resulted in lower CO2 emissions especially in the harvest. On the other hand, in the autumnwinter, the residue inputs on the ground did not reduce emissions, especially N2O. The soil remediation did not increase the accumulation of CO2, however, in the comparison between the correctives, the most CO2 emission occurred with the use of silicate. The production systems with use of fodder and green manure in winter, and the use of limestone, mainly silicate, increased productivity of corn grain per unit mass of carbon equivalent emitted into the atmosphere.